Akibat Hukum Terhadap Akta Autentik yang Dibuat dalam Keadaan Tidak Seimbang (Penyalahgunaan Keadaan) Studi Putusan Mahkamah Agung Nomor : 2319 K/Pdt/2015 - Evan Saputra Situmorang; Surya Perdana; Suprayitno Suprayitno (Universitas Medan Area, 2023)
In carrying out his position serving the community, a notary certainly pays attention to the provisions of the applicable laws and regulations and other regulations. When a notary makes a deed for the benefit of the requester, of course the notary has paid attention to various signs that can cause the deed to be canceled or null and void. But it turns out that in subsequent developments in various court decisions other legal terminology was born which emphasized that if there is a violation for certain reasons, the deed can: Has no legal force, void, illegal according to law, illegal and null and void, no legal force, cancelled. by law, invalid and has no legal force, cancelled. The existence of the legal terminology with its own reasons for doing so makes it difficult for the Notary if there is a violation no longer in the legal terminology which can be canceled or null and void by law, but also uses terminology outside the law. Abuse of circumstances exists when a person knows or must be aware that the other party due to certain circumstances, such as an emergency, dependency, rush, abnormal mental state or lack of experience, is moved to take legal action, is provoked to take legal action, or at least knowing or having to realize that the other party should be kept away from that action.